CFHTLenS and RCSLenS cross-correlation with Planck lensing detected in fourier and configuration space - Harnois-Déraps, J; Tröster, T; Hojjati, A; van Waerbeke, L; Asgari, M; Choi, A; Erben, T; Heymans, C; Hildebrandt, H; Kitching, T; Miller, L; Nakajima, R; et al. (Oxford University Press, 2016)
We measure the cross-correlation signature between the Planck CMB lensing map and the weak lensing observations from both the Red-sequence Cluster Lensing Survey (RCSLenS) and the CanadaFrance-Hawai Telescope Lensing Survey (CFHTLenS). In addition to a Fourier analysis, we include the first configuration-space detection, based on the estimators <κCMBκgal> and <κCMBγt>. Combining 747.2 deg^2 from both surveys, we find a detection significance that exceeds 4.2σ in both Fourier- and configuration-space analyses. Scaling the predictions by a free parameter A, we obtain A Planck/CFHT = 0.68 ± 0.31 and A Planck/RCS = 1.31 ± 0.33. In preparation for the next generation of measurements similar to these, we quantify the impact of different analysis choices on these results. First, since none of these estimators probes the exact same dynamical range, we improve our detection by combining them. Second, we carry out a detailed investigation on the effect of apodization, zero-padding and mask multiplication, validated on a suite of high-resolution simulations, and find that the latter produces the largest systematic bias in the cosmological interpretation. Finally, we show that residual contamination from intrinsic alignment and the effect of photometric redshift error are both largely degenerate with the characteristic signal from massive neutrinos, however the signature of baryon feedback might be easier to distinguish. The three lensing datasets are publicly available.